(untitled) (Web of Teachers: Inderscience Research, 2024)
When introducing a linguistic and cultural approach to teaching Uzbek to foreigners, it is important to create an educational environment that goes beyond the level of language knowledge and covers the rich cultural tapestry of Uzbekistan. By combining language and cultural elements in language teaching, students can gain an understanding of the traditions, customs and values of the Uzbek society, as well as gain a deeper understanding of the language. In this approach, language learning is not only vocabulary and mastering grammar, but also studying the cultural context in which the language is established. This article provides information about the linguocultural approach to teaching Uzbek to foreigners.